(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Credit appraisal is done to check the commercial, financial technical viability of the project proposed its funding pattern further checks the primary or collateral security cover available for the recovery of such funds. This study will help in understanding the credit appraisal system in banks to reduce various risk parameters, which are broadly categorized into financial risk, business risk, industrial risk management risk associated in providing any loans or advances or project finance. The study is based on secondary data.